PENDEKATAN SAINTIFIK PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN FIKIH UNTUK MENINGKATKAN KUALITAS IBADAH SISWA MTs AL ITTIHADIYAH KALIJURANG TONJONG BREBES - Saputra, Isro Wahdana; Majid, Abdul; Fatiatun, Fatiatun (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2023)
Learning activities using a scientific approach depend on the teaching teacher. A teacher must carry out his duties as a teacher to carry out and develop a scientific approach in their respective schools. Facts in the field show that the application of this scientific approach is good, but the obstacles that exist are the lack of ability of some students to read and understand Arabic letters, as well as the lack of family attention related to students' education. As for student worship in the field, the institution itself holds Dhuhr prayer activities in congregation with the aim of getting used to students, so that there are no students who do not pray Dhuhur in congregation.